Property Outlaws in Cyberspace and Meatspace? Examining the Relationship between Online Peer Production and Support for Private Property Violations - Timothy Gibson (tripleC: Communication, Capitalism & Critique)
Marxian theory has long viewed the institution of private property as central to labour exploitation. After all, private property laws allow those who control the means of production to expropriate surplus value from the dispossessed. An analogous relationship arguably defines life on the Internet, where users are forced to venture onto privately owned digital enclosures to access key services. Yet these online property relationships are anything but settled and uncontested. Outside the digital enclosures of Apple and Google, the Internet has fostered the development of “commons-based peer production”, where key resources (e.g. software) are produced without anyone claiming exclusive property rights. In fact, some scholars have argued that the rise of peer production on the web has begun to re-shape popular attitudes concerning the legitimacy of property exclusions more broadly. In short, as we become “property outlaws” on the web, we come to question the inevitability and legitimacy of private property elsewhere in life. This paper explores this hypothesis by reporting data from a survey of Internet users at an East Coast university. Are users who engage in more peer production activities on the web also more likely to approve of “property outlaw” behaviours not just in the online context, but in the offline world as well (e.g. squatting)? The data provide only partial support for the hypothesis: active online peer producers were indeed more likely to support violations of intangible (intellectual) properties, but not violations of tangible or “real-world” properties.